2018
DOI: 10.1124/jpet.118.252809
|View full text |Cite
|
Sign up to set email alerts
|

Single Dose of a Polyanhydride Particle-Based Vaccine Generates Potent Antigen-Specific Antitumor Immune Responses

Abstract: Many factors affect vaccine efficacy. One of the most salient is the frequency and intervals of vaccine administration. In this study, we assessed the vaccine administration modality for a recently reported polyanhydride-based vaccine formulation, shown to generate antitumor activity. Polyanhydride particles encapsulating ovalbumin (OVA) were prepared using a doubleemulsion technique and subcutaneously delivered to mice either as a single-dose or as prime-boost vaccine regimens in which two different time inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Through diffusion and degradation of the polymer, the drug can be released in a controlled manner to the target cancer (149). Polymers used to prepare these particles include but are not limited to poly lactic-coglycolic acid (149), polysulfenamides (150), and polyanhydrides (151). Agents that can be loaded into the particles include proteins such as cancer antigens (152), nucleic acid based molecules like plasmid DNA (153) and CpG (154) and small molecule drugs like paclitaxel and doxorubicin (149,155).…”
Section: Antibodiesmentioning
confidence: 99%
“…Through diffusion and degradation of the polymer, the drug can be released in a controlled manner to the target cancer (149). Polymers used to prepare these particles include but are not limited to poly lactic-coglycolic acid (149), polysulfenamides (150), and polyanhydrides (151). Agents that can be loaded into the particles include proteins such as cancer antigens (152), nucleic acid based molecules like plasmid DNA (153) and CpG (154) and small molecule drugs like paclitaxel and doxorubicin (149,155).…”
Section: Antibodiesmentioning
confidence: 99%
“…terms of stimulating strong immune responses, we and others have found that simultaneous delivery of the antigen and adjuvant using independently loaded particles results in similar enhancement of immune responses 17,50,54,55 . This is because separately encapsulated antigen and adjuvant will not necessarily remain segregated in vivo as both types of particle formulations could be internalized by the same DCs, which generally have the capacity to internalize more than one particle at a time 56 . Specifically, our group has previously demonstrated that co-loading PELA and OVA into the same poly(lactide-co-glycolide)-based particles generated similar cellular immune responses and provided similar tumor protection to independently loaded particles 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of survival curves was initially performed by the Log‐rank (Mantel‐Cox) test using GraphPad Prism 8 (GraphPad Software, La Jolla, CA), and further statistical analysis was carried out by pairwise comparisons, and data were analyzed using Log‐rank test (Tukey‐Kramer adjusted) using SAS 9.4 software. [ 45 ] In all tests, differences were considered statistically significant when P < 0.05.…”
Section: Methodsmentioning
confidence: 99%